2020 59th IEEE Conference on Decision and Control (CDC) 2020
DOI: 10.1109/cdc42340.2020.9304193
|View full text |Cite
|
Sign up to set email alerts
|

Learning Interaction Dynamics from Particle Trajectories and Density Evolution

Abstract: We consider the problem of understanding the coordinated movements of biological or artificial swarms. In this regard, we propose a learning scheme to estimate the coordination laws of the interacting agents from observations of the swarm's density over time. We describe the dynamics of the swarm based on pairwise interactions according to a Cucker-Smale flocking model, and express the swarm's density evolution as the solution to a system of mean-field hydrodynamic equations. We propose a new family of paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…which is the Green's function corresponding to L x in an infinite domain. We note that the parameters (k, λ , L) generate a family of interaction functions (see also (Mavridis et al, 2020)) that can simulate widely used interaction functions as the one found in the original Cucker-Smale model (Cucker and Smale, 2007):…”
Section: One-dimensional Casementioning
confidence: 99%
See 1 more Smart Citation
“…which is the Green's function corresponding to L x in an infinite domain. We note that the parameters (k, λ , L) generate a family of interaction functions (see also (Mavridis et al, 2020)) that can simulate widely used interaction functions as the one found in the original Cucker-Smale model (Cucker and Smale, 2007):…”
Section: One-dimensional Casementioning
confidence: 99%
“…In the BVP of the augmented system of PDEs (21) with the initial and boundary conditions (26), we select the linear differential operator (see also (Mavridis et al, 2020)): (66)…”
Section: Higher Dimensionsmentioning
confidence: 99%